Application of Diagnostic Tools to Evaluate Remediation Performance at Petroleum Hydrocarbon‐Impacted Sites. Issue 4 (9th October 2018) - Bouchard, Daniel; Hunkeler, Daniel; Madsen, Eugene L.; Buscheck, Tim; Daniels, Eric; Kolhatkar, Ravi; DeRito, Christopher M.; Aravena, Ramon; Thomson, Neil
Abstract: In situ treatment technologies for petroleum hydrocarbon‐impacted sites (e.g., multiphase extraction, air sparging, soil vapor extraction, or in situ chemical oxidation) usually rely on a specific chemical, microbial, or physical contaminant removal process. However, target contaminant concentrations can also vary due to other co‐occurring processes (e.g. delivery of remedial fluids, natural variability), which can confound the ability to demonstrate treatment efficiency. This technical note proposes a methodology that integrates several diagnostic tools to assess treatment performance. Stable isotope methods and biomarkers were selected because they provide process‐specific and, often, also compound‐specific information on contaminant removal. The isotope tools include compound‐specific isotope analysis that can be used to discriminate between a broad range of removal processes, and isotope analysis of oxidants and degradation end products to assess overall transformation of hydrocarbons. The biomarkers cover characteristic metabolites and functional genes on a mRNA rather than DNA level to understand biological activity more carefully. This technical note integrates information from laboratory and field studies, especially controlled‐field experiments where the tools have been evaluated side‐by‐side for different treatment methods. A tiered approach is proposed to deploy the tools in a stepwise manner until sufficient information is obtained to confidently identify the mass removal processes of interest and demonstrate efficacy of the intended treatment mechanism. The order of tool application considers the type of information that can be gained, the level of certainty, and the ease of implementation. The objective of this technical note is to enable widespread use of these diagnostic tools with the motivation to improve the efficacy of in situ treatment systems.